Ice-Flow Chronology and Palimpsest, Long-Distance Dispersal of Indicator Clasts, North of the St. Lawrence River Valley, Quebec - Veillette, Jean (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 2004)
AbstractAn ice flow model, based on the distribution of distinctive Proterozoic erratics from the Lake Mistassini and Monts Otish sedimentary basins, and on the mapping of relict striations in a 230 000 km2 area located predominantly in Grenville Province, Québec, is presented to reconstruct the evolution of a large part of the Labrador Sector of the Laurentide Ice Sheet during the Wisconsinan. The results, were added to those of similar surveys carried out in the Abitibi region, and further north. Striated surfaces and indicator clasts from an early northwestward flow, overprinted by those from a widespread southeastward flow, and lastly by those from deglaciation flows toward the southwest, south, and southeast, revealed a complex sequence of events. The northwestward flow originated from a NE‑SW, early Wisconsinan, ice divide located in the Québec highlands, south of Lake Mistassini, that migrated to a position north of the lake, at the Last Glacial Maximum, to give rise to the widespread, southeastward ice flow, that left traces over a large part of Grenville Province. Deglaciation triggered a clockwise shift in ice-flow south of Lake Mistassini, and a counterclockwise shift, north of it. Inception of the northwestward flowing glacier probably results from the coalescence of ice caps formed at the highest elevations along a narrow fringe, north of and parallel to the St. Lawrence River Valley, and expansion toward the northwest suggests a similarity with the windward growth model of ice sheet expansion. The ice flow model has implications for mineral exploration methods based on the sampling of glacial sediments.